Physicochemical Properties and Bacterial Adhesion of Conventional and 3D Printed Complete Denture PMMA Materials: An In Vitro Study – Part I - Pierre El Khoury; Naji Kharouf; Etienne Olivier; Jean-Philippe Dillenseger; Youssef Haïkel; Hatem M. El‐Damanhoury; Dariush Irani; Mutlu Özcan; Ziad Salameh (2025)
To evaluate and compare the surface morphology, wettability, roughness, and bacterial adhesion properties of polymethyl methacrylate (PMMA) materials fabricated by conventional methods and 3D printing for complete denture applications. Two PMMA materials were investigated: Conventionally processed (ProBase Hot) and 3D-printed (3DP) (V-Print Dentbase). Surface morphology (n = 3) was analyzed using scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX). Surface roughness (n = 10) was measured using an optical profilometer. Wettability was assessed through contact angle measurements (n = 6) at 10, 30, and 60 seconds. Bacterial adhesion (n = 9) and biofilm formation (n = 3) were evaluated using Escherichia coli (E. coli) as a model organism, with quantitative bacterial counts and SEM analysis of bacterial morphology. Data were statistically analyzed. Scanning electron microscopy analysis revealed nanoparticles on the surface of 3DP samples, while EDX detected silicon in these samples, absent in conventional PMMA. 3D-printed surfaces exhibited significantly lower roughness (1.05 ± 0.32 µm) compared to conventional surfaces (20.46 ± 6.71 µm) (p < 0.001). Contact angle measurements showed that 3DP surfaces were more hydrophilic (64-68°) than conventional surfaces (100°) (p < 0.05). Bacterial adhesion studies demonstrated more adherent bacteria on 3DP surfaces (92.5 ± 30.8) compared to the conventional surfaces (57.6 ± 12.5), but biofilm formation was observed only on conventional surfaces. 3D-printed PMMA exhibited distinct surface characteristics compared to conventionally processed PMMA, including the presence of silicon nanoparticles, lower surface roughness, and higher hydrophilicity. While 3DP surfaces showed higher initial bacterial adherence, in contrast, they appeared to inhibit biofilm formation, which highlights the complex nature of bacterial interactions with these materials. Further clinical studies are needed to validate the results of this investigation and generate clinical translational data. How to cite this article: Khoury P, Kharouf N, Etienne O, et al. Physicochemical Properties and Bacterial Adhesion of Conventional and 3D Printed Complete Denture PMMA Materials: An In Vitro Study - Part I. J Contemp Dent Pract 2024;25(11):1001-1008.